Augmented Experiences: Investigating the Feasibility of Virtual Reality as Part of a Workplace Wellbeing Intervention. Issue 5 (28th November 2019) - Naylor, Matthew; Morrison, Ben; Ridout, Brad; Campbell, Andrew
Abstract: : This exploratory experiment tested the effect of two virtual reality (VR) relaxation interventions on measures of physiological arousal and affect, compared to a control. Forty-nine participants were randomly assigned to one of three conditions, all using the Oculus Rift. Participants wore a heart rate (HR) monitor and completed pre- and post-test surveys, including the positive and negative affect schedule, Likert-type and open feedback questions. Mixed repeated measures ANOVAs revealed significant reductions in HR and affect over time across all conditions, with a significant interaction identified for the breathing condition's effect on negative affect. Participants were able to identify feeling relaxation, as well as influencing factors. Further, the majority expected, and supported, the introduction of VR interventions in their workplace and/or college, with privacy being a common concern. These results demonstrate the potential of VR augmented relaxation interventions with recommendations for further study provided. RESEARCH HIGHLIGHTS: VR can potentially provide wellbeing interventions with a uniquely immersive quality Results suggest interactive and immersive VR experiences may facilitate relaxation and reduce stress Participants believe there may be substantial benefits to having VR wellbeing interventions at work and college.